HYDRODYNAMIC ASPECTS OF THE FORMATION AND DISINTEGRATION PROCESSES OF FUEL FILM CREATED BY THE INJECTOR OF THE COMBUSTION CHAMBER OF AN AIRCRAFT ENGINE - Kostarev, K.G.; Batalov, V.G.; Mizev, A.I.; Sukhanovskii, AN.; Shmyrov, A.V. (Perm Federal Research Centre Journal, 2017)
The paper presents the results of an experimental study of a model liquid dispersion by the injector of an aircraft engine with the aim of improving its operation. Particular attention is focused on the processes of formation and subsequent disintegration of the liquid film into isolated droplets, which are investigated by optical techniques. The investigation conducted allowed us to determine the reasons for the onset of different types of instabilities of the film shape leading to its premature and asymmetric destruction and to assess the influence of such factors as the number of atomizer injectors, the degree of wetting the inner injector surface, the pressure of the liquid in the trunk of the injector and the intensity of its external air blowing.